Organizational noises in the modern paradigm: a carnivalesqued reading - Ahmad, Che Mahzan (INSI Publications, 2011)
The purpose of this article is to apply Bakhtin theory of carnivalesque as a device in reading noises of the displaced other during a change program in an organization that rests solely upon the modernist approach. The change divided the organization into two worlds. In the ‘first world’noises are centripetalised around monologism, and it can be seen via sobornost. In the ‘second world’,where the displaced other reside, noises are centrifugalised with play as its main agent. They play the subversive game of halus and kotor in the back region in order to create madness over the marginalization. We suggest the displaced other noises be recovered as Serresian noises that live on parasite logic, and authoring the project should be viewed as signed deed without alibi, and it must be managed with Bakhtinian ethics of otvetsvennost. This paper attempts to explore Bakhtin’s contribution for understanding change dynamics.